Language in conflict debates: Impoliteness strategies in the open to debate youtube channel ‘were Israel’s actions in the Gaza war justified?’ - Intan Nur'aini; Hilmi Akmal (Journal of Language and Pragmatics Studies, 2025)
This study analyzes the strategies of impoliteness in the debate ‘Were Israel’s Actions in the Gaza War Justified?’ on the Open to Debate YouTube channel. Using Jonathan Culpeper’s theory of impoliteness, this research aims to identify and analyze the impoliteness strategies employed by speakers and their functions in the context of conflict debates. This qualitative study utilizes documentation techniques and data cards to collect and analyze data. The results show that there are 4 instances of bald on record, 2 instances of sarcasm or mock politeness, and 1 instance of negative impoliteness, and 1 instance of positive impoliteness. Further analysis reveals that these impoliteness strategies can be categorized into two primary functions: coercive impoliteness (pressuring the opponent) and affective impoliteness (expressing strong emotions). This study also demonstrates that impoliteness in debates about conflict does not only carry negative connotations, but also can serve as a form of strong concern for defending humanity and as an effort to voice concerns for the conflict resolution. In conclusion, this study shows that the three speakers (Eylon Levy and Mehdi Hasan) employ impoliteness strategies with different objectives: Eylon Levy tends to prioritize Israel’s security, while Mehdi Hasan uses impoliteness to defend all victims, both in Palestine and Israel, and to support conflict resolution.